Using biophysical modelling and population genetics for conservation and management of an exploited species, Pecten maximus L. (2nd July 2021) - Hold, Natalie; Robins, Peter; Szostek, Claire L.; Lambert, Gwladys; Lincoln, Harriet; Le Vay, Lewis; Bell, Ewen; Kaiser, Michel J.
Abstract: Connectivity between populations is important when considering conservation or the management of exploitation of vulnerable species. We investigated how populations of a broadcast‐spawning marine species (scallop, Pecten maximus ) that occur in discrete geographic locations were connected to each other. Population genetic insights were related to the outputs from a three‐dimensional hydrodynamic model implemented with scallop larval behaviour to understand the extent to which these areas were linked by oceanographic processes and how this was altered by season and two contrasting years that had strongly different average temperature records (warm vs cold) to provide contrasting oceanographic conditions. Our results span from regional to shelf scale. Connectivity was high at a regional level (e.g. northern Irish Sea), but lower at scales >100 km between sites. Some localities were possibly isolated thus dependent on self‐recruitment to sustain local populations. Seasonal timing of spawning and inter‐annual fluctuations in seawater temperature influenced connectivity patterns, and hence will affect spatial recruitment. Summer rather than spring spawning increased connectivity among some populations, due to the seasonal strengthening of temperature‐driven currents. Furthermore, the warm year resulted in higher levels of modelled connectivity than the cold year. The combination of genetic and oceanographic approaches provided valuable insights into the structure and connectivity at a continental shelf scale. This insight provides a powerful basis for defining conservation management units and the appropriate scale for spatial management. Temporal fluctuations in temperature impact upon variability in connectivity, suggesting that future work should account for ocean warming when investigating population resilience.